Developmental and adapted physical education : making ability count - Horvat, Michael A., 1947-; Eichstaedt, Carl B. (New York : Routledge, 2019)
Now in a fully revised and updated 6th edition, reflecting changes in legislation and cutting-edge research, this is a complete introduction to adapted physical education, from the underpinning science to practical teaching strategies and program design. The book covers a broader range of disabilities, developmental disorders, and health conditions than any other textbook and includes brand new material on developmental coordination disorders and cognitive development. Full of teaching and coaching strategies and techniques, it introduces scientific fundamentals, key legislation, and best practice in designing effective programs. It encourages the reader to consider the individual before the disability and to focus on what learners can do rather than what they can't. This is an essential reference for teachers, coaches, or exercise professionals working with children with disabilities. It is also an invaluable resource for undergraduate or postgraduate students of adapted physical education, kinesiology, physical education, physical therapy, exercise science, athletic training, or sports coaching. The new edition features updated online resources, including PowerPoint slides, web links, an example syllabus, and quizzes.
Section VI Developing and implementing the physical activity program20 Behavior management; 21 Teaching physical fitness; 22 Teaching motor skills; 23 Teaching adapted aquatics; 24 Coaching and sport for persons with disabilities; Index
Revised edition of Developmental/adapted physical education / Carl B. Eichstaedt. 3rd ed. 1993.
OCLC-licensed vendor bibliographic record.
Keywords: Physical education for people with disabilities -- United States; Mainstreaming in education -- United States; SPORTS & RECREATION / Business Aspects; SPORTS & RECREATION / Essays; SPORTS & RECREATION / History; SPORTS & RECREATION / Reference; EDUCATION / Special Education / General; EDUCATION / Physical Education; MEDICAL / Pediatrics